2017
DOI: 10.1016/j.neubiorev.2017.04.017
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between central and peripheral oxytocin concentrations: A systematic review and meta-analysis

Abstract: There is growing interest in the role of the oxytocin system in social cognition and behavior. Peripheral oxytocin concentrations are regularly used to approximate central concentrations in psychiatric research, however, the validity of this approach is unclear. Here we conducted a pre-registered systematic search and meta-analysis of correlations between central and peripheral oxytocin concentrations. A search of databases yielded 17 eligible studies, resulting in a total sample size of 516 participants and s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
104
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(108 citation statements)
references
References 48 publications
4
104
0
Order By: Relevance
“…The studies included in the review have limitations that call for caution in the interpretation and generalization of their findings, including (a) small sample sizes recruited from extremely specific contexts; (b) poor control of confounding variables such as gender and ET severity; (c) highly variable age groups; (d) cross-sectional designs; (e) possible differences between chronic and acute administration of OXT in RCT; and (f) lack of evaluation of both central and peripheral levels of OXT to determine whether differences exist [most of the studies on this topic assessed endogenous levels in peripheral fluids (e.g., blood plasma, urine, saliva) and the methodological validity of these techniques is controversial (Wotjak et al, 1998 ; Seltzer et al, 2014 ; Valstad et al, 2017 )].…”
Section: Discussionmentioning
confidence: 99%
“…The studies included in the review have limitations that call for caution in the interpretation and generalization of their findings, including (a) small sample sizes recruited from extremely specific contexts; (b) poor control of confounding variables such as gender and ET severity; (c) highly variable age groups; (d) cross-sectional designs; (e) possible differences between chronic and acute administration of OXT in RCT; and (f) lack of evaluation of both central and peripheral levels of OXT to determine whether differences exist [most of the studies on this topic assessed endogenous levels in peripheral fluids (e.g., blood plasma, urine, saliva) and the methodological validity of these techniques is controversial (Wotjak et al, 1998 ; Seltzer et al, 2014 ; Valstad et al, 2017 )].…”
Section: Discussionmentioning
confidence: 99%
“…This study used group activities to stimulate endogenous OT release and relate the change in OT to in- and out-group bias. While basal plasma OT and central OT are unrelated, after stimulation, the change in OT in plasma and cerebral spinal fluid are positively correlated across several studies (Neumann et al, 2013 ; Valstad et al, 2017 ). Taking this into account, the analysis here only uses the percent change in OT in plasma to reflect the effects of central OT.…”
Section: Methodsmentioning
confidence: 95%
“…A recent meta-analysis by Valstad et al (2017) confirmed that inhaled OT constitutes a reliable and harmless way to manipulate participants’ OT brain levels. However, several recent reviews identified relatively poor replicability within the OT literature ( Nave et al , 2015 ; Leng and Ludwig, 2016 ; Walum et al , 2016 ), which partly arises from small sample sizes.…”
Section: Methodsmentioning
confidence: 99%